The foundation of the rhubarb industry economy: investigating metabolites disparities of rhubarb between varieties and growing environments on the Tibetan plate - Zou, Jinpeng; Wu, Wei; Wang, Fang; Hou, Kai (Frontiers in Pharmacology, 2024)
Objective In Tibetan dietary and folk medicine practices, R. austral is commonly used as an alternative to R. tanguticum, and there is a prevailing belief that wild rhubarb should not be substituted by its cultivated counterpart. However, these traditions are not supported by scientific evidence, particularly concerning the differences in endogenous metabolites between cultivated and wild rhubarbs, as well as between officially recognized and non-official rhubarbs.Methods In this study, ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-QTOFMS) and biostatistical analysis were employed to systematically and comprehensively investigate the chemical constituents of rhubarbs from various sources, focusing on the differences in metabolic components between cultivated and wild rhubarbs.The metabolic differences in rhubarb from various varieties and environments are pronounced. Among them, 39 differential metabolites were identified between cultivated R. tanguticum and wild R. tanguticum. cultivated R. tanguticum is rich in emodin, physcion, and rhapontigenin, whereas wild R. tanguticum exhibits a higher concentration of rhaponticin and is particularly abundant in anthraquinone compounds. Additionally, 33 differential metabolites distinguished wild R. tanguticum from wild R. austral, with R. austral being rich in stilbene 2 derivatives and wild R. tanguticum predominantly containing coumarins. The correlations among these differential metabolites have also been further explored and presented.The metabolic disparities between cultivated and wild rhubarb varieties are substantial, with wild rhuabarb containing higher levels of effective components than its cultivated counterparts.However, wild varieties face issues with component instability and resource depletion, while cultivated varieties exhibit more stable effective components. Given these significant differences in metabolic components, it is essential to differentiate rhubarbs from various species and growing conditions to suit specific medicinal and dietary purposes effectively.